Enzymatic Modification of Bacterial Receptors on Saliva-Treated Hydroxyapatite Surfaces - Gibbons, R. J. (1982)
Certain properties of experimental pellicles formed by the adsorption of salivary components on hydroxyapatite surfaces change over time. To determine whether enzymes likely to be present in the oral environment could induce such changes, pellicles were treated with saliva which had been incubated for 18 h at 35°C to promote the elaboration of microbial enzymes. This treatment markedly reduced the numbers of Streptococcus mutans MT3 and JBP and S. sanguis FC-1 and C5 cells which attached, but it had little or no effect on the attachment of S. mitis RE7, Actinomyces viscosus LY7 and CK-8, Bacteroides gingivalis 381, or B. melaninogenicus subsp. intermedius 581. Heating the incubated saliva at 60°C for 30 min partially reduced its pellicle-modifying activity, whereas heating at 80°C for 30 min or 100°C for 15 min completely eliminated such activity. This indicated that the saliva contained heat-labile substances, presumably enzymes, which could affect the pellicle receptors involved in the attachment of S. mutans and S. sanguis. Treatment of saliva-treated hydroxyapatite with commercially obtained enzyme preparations also affected bacterial attachment. Thus, treatment with galactose oxidase reduced the numbers of the S. mutans strains which attached, whereas treatment with neuraminidase reduced the adsorption of S. sanguis FC-1 but not that of S. sanguis C5. Treatment with β-glucosidase preparations derived from almonds significantly reduced the attachment of all of the streptococcal strains studied, but, when subjected to isoelectric fractionation, the adherence-inhibiting activity did not correlate directly with β-glucosidase activity. Treatment of the pellicles with trypsin or eight other glycosidases did not affect streptococcal attachment. Exposure of the enzymatically modified pellicles to fresh saliva did not restore the streptococcal receptors. Collectively, the data suggest that some bacterial receptors in the pellicle coating of teeth can be modified by enzymes likely to be present in the oral environment, and these interactions may affect oral bacterial ecology.